2022
DOI: 10.1177/02666669221101574
|View full text |Cite
|
Sign up to set email alerts
|

Electronic records management in Tanzanian courts

Abstract: Conventional records management systems are mostly used to support court operations and service delivery in Tanzania despite the substantial development of ICTs. The objectives of this study were to: examine types of e-records managed, explore staff perceptions of the usefulness of e-records management, and analyse factors limiting electronic records management in selected courts. A survey design comprising qualitative and quantitative research approaches was employed to meet these objectives. Standardised que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study by Romwald & Mwantimwa (2020) found that paper-based records management systems are still the most commonly used, indicating that it is not as effective as expected. Another study by Hassan & Mwantimwa (2022) found that e-filings system was ineffective. However, the previous studies did not give enough consideration to such aspects as dimensions of quality judicial service delivery through e-filing, duration, accessibility and convenience of the judicial services delivered through e-filing.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Romwald & Mwantimwa (2020) found that paper-based records management systems are still the most commonly used, indicating that it is not as effective as expected. Another study by Hassan & Mwantimwa (2022) found that e-filings system was ineffective. However, the previous studies did not give enough consideration to such aspects as dimensions of quality judicial service delivery through e-filing, duration, accessibility and convenience of the judicial services delivered through e-filing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pumulo (2012) indicates that courts of law in Zambia are battling with managing both physical and electronic records, which affect the delivery of justice and duration of cases. Odeyemi, Issa and Saka (2011), Ladan (2014), Mboya (2019) andHassan, Dotto andMwantimwa (2022) state that courts in Tanzania and Nigeria have a massive backlog of court cases that have delayed progress of hundreds of thousands of criminal cases because of ineffective management of electronic records. Furthermore, Maseh (2015), Nafula (2018) and Wanjiru and Learning (2022) advocate that Kenyan Judiciary experiences several challenges such as backlogs of cases, lost, misfiled, or damaged files, and delays in registering cases because of poor recordkeeping practices.…”
Section: Introduction and Background To The Studymentioning
confidence: 99%